Relationship between type 2 diabetes mellitus, postural balance, and the risk of falls in older adults (CIPEEX, 2025)
Older adults with diabetes mellitus have reduced muscle mass, which increases their risk of falls and, consequently, their fear of falling. The aim of this study is to conduct an integrative literature review to analyze the relationship between type 2 diabetes mellitus, postural balance, and the risk of falls in older adults. The PubMed, Scopus, LILACS, and SciELO databases were consulted using the terms "Type 2 Diabetes Mellitus," "postural balance," "falls," "elderly," and "balance and elderly"; "balance and elderly and falls"; "balance and elderly and falls and diabetes mellitus." The inclusion criteria defined for the selection of articles were articles published in Portuguese and English, full-text articles that addressed the theme of the integrative review, and articles published and indexed in the aforementioned databases. Older adults with type 2 diabetes have a greater fear and risk of falls and postural balance problems, especially those who use insulin or other medications.
Keywords: Elderly; diabetes mellitus; postural balance; falls